If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -4) = 8(x + 2) Reorder the terms: 6(-4 + 2x) = 8(x + 2) (-4 * 6 + 2x * 6) = 8(x + 2) (-24 + 12x) = 8(x + 2) Reorder the terms: -24 + 12x = 8(2 + x) -24 + 12x = (2 * 8 + x * 8) -24 + 12x = (16 + 8x) Solving -24 + 12x = 16 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -24 + 12x + -8x = 16 + 8x + -8x Combine like terms: 12x + -8x = 4x -24 + 4x = 16 + 8x + -8x Combine like terms: 8x + -8x = 0 -24 + 4x = 16 + 0 -24 + 4x = 16 Add '24' to each side of the equation. -24 + 24 + 4x = 16 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = 16 + 24 4x = 16 + 24 Combine like terms: 16 + 24 = 40 4x = 40 Divide each side by '4'. x = 10 Simplifying x = 10
| 4(x-4)-1=-5(-5x+5)-7x | | (10x^3-18x^2)/2x^2 | | 3+2ab-4ac+6bc= | | 2(x-2)+2x=4 | | (X-19)+17=63 | | -24b=-48 | | 1p^2+2p-24=0 | | 7(b+10)= | | -2/3n-4=5 | | (x+16)(x-18)=180 | | 4x+10=3x-4 | | -2(u+1)=-2(9u-7)+4u | | 3(-2+7x)=-27 | | 1250w^10z^5/20w^2z^2 | | 2z+7=3z-11 | | 1-5x=6x-10 | | 3(u+2)+2u=7(u-1)+1 | | 3x+2(3x+5)-4(3x+4)+3(3x+2)+8=0 | | (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x | | -3.2b+6=-5.1 | | 4(3x-1)=45 | | 2x^2+7=8x | | -5-2x+x=3 | | -2500-4.05=3000 | | -5(x+12)-13-=-24 |